Review of the Book: Juvelirnye ukrashenija tjurkskih narodov Evrazii [Jewelry of Turkic Peoples of Eurasia] (Kazan, 2018) - Zhilina N.V. (Золотоордынское обозрение)
This article analyzes a new book by a group of authors dedicated to jewelry of the Turkic peoples of Eurasia. The study of extensive jewelry materials of the Turkic peoples of the 18th–20th centuries is important for specialists emerging from different profiles (ethnographers, archeologists, art historians, historians) as well as for interdisciplinary research related to the study of the culture of different nations. This study, and the new ones it stimulates, will help to clarify the historical paths of development and of cultural interaction between nations. The main content of the book is based on the principle of consistent characterization of jewelry and art of various Turkic peoples: six chapters. The book characterizes the forms of jewelry, their semantics, technology, and use in national costumes. Unfortunately, the task of studying the ornamentation of jewelry has not been set. One chapter raises the general problem of the symbolic meaning of metals in the mythology of the Turks and Mongols. The book can become a real corpus of sources only after the publication of a catalog of the materials studied in a desired second volume. The use of the typological method in the book is not always consistent and clear. While the book is colorfully illustrated, there is a lack of typological tables among the illustrations. The authors are often inclined to link earlier materials to the ones they discuss in the book. Despite some analogies, for objective comparison there is a lack of complete knowledge of the entire body of materials: typological, technological and stylistic. Each of the authors touched the stated aspects of jewelry problems with different degrees of breadth and depth. Such a situation is partly justified by the fact that the genre of this book is defined as “historical and ethnographic essays”. One of the best chapters of the book, in our opinion, is the chapter of A.I. Savvinov about jewelry of the Yakuts, fully relevant to the objective of the book. Among the strong works, there is the chapter by L.N. Donina and S.V. Suslova about the Kazan-Tatar jewelry art with a detailed analysis of the technology. A common feature of the collective monograph is the lack of output sections of chapters. Despite the noted shortcomings, the published book can be welcomed as an accomplished exercise in performing a complex task – setting out the characteristics of the jewelry of various Turkic peoples. My focusing on some questions, I hope, will serve in fruitful discussions. In addition to the idea already realized, it is possible to hope for the release of the second volume of the book with a catalog of the main materials, as well as with some analytical and concluding chapters or sections.